2020
DOI: 10.21203/rs.3.rs-36491/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Galuteolin suppresses proliferation and inflammation in TNF-α-induced RA-FLS cells by activating HMOX1 to regulate IKKβ/NF-κB pathway

Abstract: Objective: Galuteolin (Galu) is a substance extracted and purified from honeysuckle. The purpose of this study was to explore the effects of Galu on the TNF-α-induced RA-FLS cells (synoviocytes) and reveal its potential molecular mechanism from the perspectives of anti-apoptosis and anti-inflammation.Methods: After TNF-α stimulation, cell proliferation of RA-FLS was assessed by CCK-8 assay. TUNEL staining was used to detect the apoptosis. Western Blot was used to detect the expressions of Iκκβ, p-p65, p65, p-I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…than those elicited from their younger counterpart [48]. In addition, IκB and NF-κB could mediate various signaling pathways including proliferation, apoptosis, and inflammation [49,50]. A recent study also demonstrated that the application of pyrrolidine dithiocarbamate (PDTC), a NF-κB inhibitor, provides a potential therapeutic strategy for TNF-αinduced muscle atrophy [51].…”
Section: Discussionmentioning
confidence: 99%
“…than those elicited from their younger counterpart [48]. In addition, IκB and NF-κB could mediate various signaling pathways including proliferation, apoptosis, and inflammation [49,50]. A recent study also demonstrated that the application of pyrrolidine dithiocarbamate (PDTC), a NF-κB inhibitor, provides a potential therapeutic strategy for TNF-αinduced muscle atrophy [51].…”
Section: Discussionmentioning
confidence: 99%